THE EFFECTIVENESS OF LAW NUMBER 12 YEAR 1951 AGAINST THE USE OF FIREARMS IN MAKASSAR FROM THE SOCIOLOGY OF LAW PERSPECTIVE - Anggelita Fuji Lestari; Muhadar; Audyna Mayasari Muin (Awang Long Law Review, 2022)
This study aims to analyze the effectiveness of Law Number 12 Year 1951 in preventing the misuse of firearms in Makassar from the perspective of legal sociology. This research is sociological legal research. Sources of data in this study are direct interviews with respondents as the primary data source and literature study as a secondary data source. The collected data was then analyzed qualitatively. This study shows that (1) The effectiveness of Law Number 12 Year 1951 in preventing the misuse of firearms in Makassar City from the perspective of legal sociology is still less effective because seen from the licensing and control procedures for firearms, it is very strict but in the application of sanctions that do not the maximum and even in many cases the application of sanctions is less than half of the maximum threat as regulated in the Law Number 12 Year 1951; and (2) Obstacles faced in implementing the Law Number 12 Year 1951 concerning firearms in Makassar are due to law factors, law enforcement officials, facilities and infrastructure factors, cultural factors, and community factors. Among these five factors, cultural factors are quite influential in the effectiveness of law enforcement against the misuse of firearms in Makassar, it can be seen that cultural factors can actually encourage others to commit crimes.